Can civil society be free of the natural state? Applying north to Bangladesh - Geof Wood (University of Bath, Centre for Development Studies (CDS), 2014)
The recent book on 'Violence and Social Orders' by the Nobel Prize winner Douglass North and others distinguishes between limited access and open access states. Most states in the world remain limited access, or natural, states dominated by coalitions of elites capturing rents from the society while limiting access of ordinary people. A feature of natural states, whether fragile, basic or mature, is that organisations in the society are unable to exist and function independently of the state, which is represented either by dominant individual rulers or by a broader social persona or political class. There are parallel theoretical approaches to express this lack of independence, for example: the contrast between normative approach of de Tocqueville and the scepticism of Gramsci; the discourses on syndicalism and corporatism, especially associated with authoritarian decades in Latin America; and, for societies like Bangladesh, whether the presence of Ummah undermines any prospect of conceiving civil society independently of the state. Being so heavily aid dependent in the recent past, civil society organisations in Bangladesh, especially the development NGOs, have also reflected a western normative discourse about open access states and critical independence which is rarely realised in practice, while crowding out other more indigenous forms of social capital. The paper will review some case examples of failure, compromise and apparent success among CSOs to reveal the tension between voice and loyalty, and ask whether Bangladesh will continue to be a natural state regime for the foreseeable future, combining elements of fascism, populism, syndicalism and tight control of access to rents. The analysis has to be subtle, drawing upon ethnographical insights, particular events as well as structural conditions and processes.
Keywords: 330; Natural state; civil society; development NGOs; Ummah; ethnography; Bangladesh